Features of cognitive productivity of children in competitive and recovery periods. - Gant Н.E (Kharkov National Pedagogical University, 2011)
Features of mental capacity of children of secondary school age in a competitive activity. A psycho diagnostic examination of children of school age (10-15 years) has been systematically engaged in rock climbing. The features of cognitive efficiency of athletes in a competitive and recovery activities. The features of cognitive efficiency of athletes in competitive and recovery activities. Found that decreasing cognitive efficiency in children of secondary school age, in terms of competitive activity, are functional in nature and amenable to the reduction in early recovery period.